2021
DOI: 10.3390/nu13113682
|View full text |Cite
|
Sign up to set email alerts
|

Effect of COVID-19 Pandemic-Induced Dietary and Lifestyle Changes and Their Associations with Perceived Health Status and Self-Reported Body Weight Changes in India: A Cross-Sectional Survey

Abstract: Home confinement during the COVID-19 pandemic is accompanied by dramatic changes in lifestyle and dietary behaviors that can significantly influence health. We conducted an online cross-sectional survey to assess COVID-19 pandemic-induced dietary and lifestyle changes and their association with perceived health status and self-reported body weight changes among 1000 Indian adults in early 2021. Positive improvements in dietary habits, e.g., eating more nutritious (85% of participants) and home-cooked food (89%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 58 publications
0
21
1
Order By: Relevance
“…A review published in India emphasized lifestyle behavioral programs using e-Platform to improve the lifestyle of youth during such lockdowns [18]. There are limited studies done in India [2,[19][20][21][22] showing the pattern of diet and lifestyle change among college students as an impact of lockdown due to ongoing pandemic. Therefore, the present study aimed to check the same among college students of east India with the objectives to find out the proportion of college students having a change in lifestyle and dietary pattern before and during lockdown to contain the spread of COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…A review published in India emphasized lifestyle behavioral programs using e-Platform to improve the lifestyle of youth during such lockdowns [18]. There are limited studies done in India [2,[19][20][21][22] showing the pattern of diet and lifestyle change among college students as an impact of lockdown due to ongoing pandemic. Therefore, the present study aimed to check the same among college students of east India with the objectives to find out the proportion of college students having a change in lifestyle and dietary pattern before and during lockdown to contain the spread of COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…There were changes in body weight and eating amount in our study population, like in other studies during the COVID-19 pandemic. 14,[18][19][20] Our study showed that changes in body weight and eating habits were significantly associated with age. A study by Di Renzo et al found that younger people took more night snacks and declared increased appetite.…”
Section: Discussionmentioning
confidence: 60%
“…According to Song's prediction model, a 4.3-year delay in nalizing sodium targets in the United States may cost over 250 000 lives by 2031 [28]. For now, the COVID-19 pandemic has not only stressed the healthcare systems, but also changed lifestyles due to social isolation, including an increase in consumption of unhealthy products [29]. It is vital for policy-makers to take actions to raise awareness of salt reduction among the public as well as to maximize industry compliance with the sodium-reduction targets as soon as possible.…”
Section: Discussionmentioning
confidence: 99%